Navigating social distance in foundational clinical encounters: Understanding medical students' early experiences with diverse patients. (2nd September 2018) - Roberts-MacDonald, Miesha; Razack, Saleem
Abstract: Background: Social distance between patients and physicians has been shown to affect the quality of care that patients receive. Little is known about how social distance between students and patients is experienced by learners during early clinical exposures in medical school. Objective: This study aims to explore students' stories of experiencing social distance with patients with concordant and discordant social characteristics as themselves, respectively, as well as students' needs from medical curricula regarding developing social competence. Methods: Semi-structured interviews of medical students [ n  = 16] were performed, and a post-interview survey and a visual analog scale were completed. The interviews were audio-recorded and transcribed. The written transcripts were coded using the constant comparison method and analyzed for emerging themes. Results: Students experience social distance with patients; yet, they are not taught explicitly by their preceptors how to manage these experiences. Students identified their needs for the curriculum in regard to developing social competence and proposed various strategies and curriculum recommendations. Conclusions: Our results support that students believe that social competence training is important for their professional development to improve relationship-building with diverse patients. As such, it would be valuable to incorporate student recommendations in the formation of a social competence curriculum.